Resurrection, revision and molecular phylogenetics of Eragenia Banks with implications for Ageniellini systematics (Hymenoptera: Pompilidae). (17th October 2014) - WAICHERT, CECILIA; VON DOHLEN, CAROL D.; PITTS, JAMES P.
Abstract Priocnemella Banks is a small Neotropical genus within Ageniellini with remarkable morphological variation between species. Some species are small and variable in colour, whereas others are large with black integument and yellow wings. We conducted a phylogenetic analysis of Priocnemella based on the mitochondrial gene cytochrome oxidase I and the nuclear marker long‐wavelength rhodopsin. Our results indicated that Priocnemella is a paraphyletic genus. Based on molecular phylogenetic analyses, we discuss the taxonomic validity of Priocnemella, its implications and a new circumscription of genera of Ageniellini. Eragenia Banks is revalidated (stat. rev.) and applied to 16 species, eight of which are newly described: Eragenia bella Waichert & Pitts sp.n., E. carinata Waichert & Pitts sp.n., E. dentata Waichert & Pitts sp.n., E. oliva Waichert & Pitts sp.n., E. pseudomicans Waichert & Pitts sp.n., E. setosa Waichert & Pitts sp.n., E. rotunda Waichert & Pitts sp.n., E. villosa Waichert & Pitts sp.n., E. abdominalis (Smith), E. amabilis (Taschenberg), E. aureicornis (Smith), E. coerulipes (Smith), E. congrua (Fox), E. isolata (Banks), E. micans (Fabricius), and E. tabascoensis (Cameron). Priocnemella fairchildi (Banks), P. insignis (Banks), P. eurytheme Banks, P. hexagona (Fox) and P. hexagona omissa Banks maintain their generic status. Phanochilus Banks is considered a junior synonym of Priocnemella and the following species are newly placed within Priocnemella: P. fuscomarginata (Fox), P. gloriosa (Smith), P. nobilitata (Smith) and P. ornata (Banks). The following nomenclatural changes are proposed: Priocnemella rufothorax (Banks) is synonymized under Eragenia micans (Fabricius) (syn. n.); Priocnemella delila (Banks), Priocnemella bequaerti (Banks) and Priocnemella infelix (Banks) are junior synonyms of Eragenia aureicornis (Smith) (syn.n.) (comb.n). New combinations are proposed for Eragenia aureicornis (Smith) comb.n., Eragenia abdominalis (Smith) comb.n. and Eragenia coerulipes (Smith) comb.n. from Agenia; and Eragenia congrua (Fox) comb.n. from Salius. A neotype is designated for E. coerulipes and for E. tabascoensis. Divergence dates between species of Eragenia, ancestral areas and pattern of dispersal that shaped the current geographic distribution are discussed. The genus is about 9.8 Ma old, originating in Mesoamerica during the Miocene. Finally, newly described male genitalic characters are discussed and illustrated, and illustrated keys for males and females species of Eragenia are provided. This work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:8308D00F‐E25E‐4019‐A94B‐DCAEDED67D4C.